2016
DOI: 10.1039/c5ta08297h
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial nitrogen stabilizes carbon-coated mesoporous silicon particle anodes

Abstract: We report for the first time that the interfacial Si–N–C layer could stabilize the solid–electrolyte interphase of a cabon-coated mesoporous silicon particle anode and enable 100% capacity retention after 400 cycles at 0.1 A g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Hassan et al used Si–sulfur–graphene to develop a robust hierarchical nanoarchitecture, which prevented agglomeration of Si, stabilized the electrode and SEIs, leading to a superior reversible capacity of over 1000 mA h g −1 for 2275 cycles at 2 A g −1 . Han et al prepared mesoporous Si particles encapsulated in the interfacial Si–N–C layer to enhance interactions between Si and carbon as well as to form a stable SEI layer, which resulted in a high electrochemical performance . Sun et al showed that by tailoring the Si–carbon interface with atomic oxygen, the cycle life of Si/C composite electrodes can be improved by 300% even at high mass loadings …”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al used Si–sulfur–graphene to develop a robust hierarchical nanoarchitecture, which prevented agglomeration of Si, stabilized the electrode and SEIs, leading to a superior reversible capacity of over 1000 mA h g −1 for 2275 cycles at 2 A g −1 . Han et al prepared mesoporous Si particles encapsulated in the interfacial Si–N–C layer to enhance interactions between Si and carbon as well as to form a stable SEI layer, which resulted in a high electrochemical performance . Sun et al showed that by tailoring the Si–carbon interface with atomic oxygen, the cycle life of Si/C composite electrodes can be improved by 300% even at high mass loadings …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the higher discharge plateau indicates the less polarization of Si/MoSi 2 electrode. 42 directly, while the Si/MoSi 2 electrode could still maintained a reversible capacity of ~550 mAh g -1 . When the current density was returned back to 0.1C after high rate test, the capacities of both electrodes resumed.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be ascribed to an activation process during the first several cycles. In addition, the higher discharge plateau indicates less polarization of the Si/MoSi 2 electrode. , As a result, the existence of MoSi 2 particles has positive effects on the electrical conductivity of electrodes. Cycling performance of bare Si and Si/MoSi 2 electrodes tested at a rate of 0.2 C was provided in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…The atomic radius similar to carbon and the electron‐rich nature makes N‐doped carbon exhibit lots of unique electronic properties from the pure carbon . Multifarious N‐containing precursors such as polypyrrole (PPy), polydopamine (PDA), and polyacrylonitrile (PAN) are widely used as nitrogen‐containing carbon coating layers on Si‐based materials . In this section, we will briefly introduce the preparation of the above mentioned three types coating materials as well as their applications in Si/C composite anode materials.…”
Section: Nitrogen Dopingmentioning
confidence: 99%